Arbetsprov i fält på ridhästar - Östlund, Viktoria (2009)
Sport horses are widely used for performance in jumping, dressage, endurance etc. To enable comparisons of horses, training facilities, programs or physical status, an exercise test can be used. Exercise tests are also important to increase knowledge about exercise physiology of the horse considering different ways of training to compare training methods or individual qualities, development of an individual or other investigations of equine exercise physiology.